The Quest for an Effective Dengue Vaccine: Hope or Hype (Journal of Medicine, 2024)
Several trials are ongoing to develop a safe and effective vaccine to prevent dengue virus (DENV) infections, especially avoiding the risk of antibody-dependent enhancement. Only three of them (Dengvaxia/CYTTDV, Takeda TAK-003, and NIH TV-003/TV-005) have shown promising results. The issue of ‘hyperendemicity’ and ‘quasi-species the major challenge behind developing a successful vaccine. The overall efficacy of first successful vaccine ‘Dengvaxia’ showed 30.2%–60.8% efficacy with limited protection against DEN 1 and DEN 2. In Bangladesh, since 2019, outbreaks have mostly been caused by DEN 2 and DEN 3, and the trend is predicted to continue for the coming years. TAK-003 gives almost no protection against DEN 3, which is the most notorious serotype encircling Bangladesh. The overall efficacy of this vaccine is 62%, with limited protection against DEN 4. NIH TV-003/TV-005 currently shows more promise with an overall efficacy of 80%. However, we have to wait until June 2024 for the final results. All of these vaccines are safe and effective for travelers. However, for mass vaccination, a country should make a decision based on their prevalent serotypes and the potential serotypes that might cause the next epidemic. To gather these data, a robust serotype- and genotype-based surveillance system and warning system should be in place.J MEDICINE 2024; 25: 58-67